A closer look at the association between African American men’s perceptions of healthcare providers’ cultural sensitivity and hypertension - Kyvia Crisco (The Beryl Institute, 2021)
African Americans, specifically African American men, continue to have a substantially higher rate of hypertension and lower life expectancy than other racial and ethnic groups. This has been linked to poor interactions with health care providers. The purpose of this study was to examine the association between African American men's perceptions of health care providers' cultural sensitivity and a diagnosis of hypertension. A cross-sectional quantitative study was conducted with a specific focus on the association between the perceptions of provider cultural sensitivity and hypertension controlling for age, socioeconomic status, insurance status, and anxiety. Quantitative data were collected from 330 African American men using a modified NHIS (National Health Interview Survey) questionnaire consisting of an 18-question multiple-choice and Likert-scale survey. A logistic regression analysis was conducted to predict hypertension from age, socioeconomic status, insurance status, anxiety, and perception of provider cultural sensitivity. The overall model was significant and explained 11.7% of the variance in hypertension. Age and anxiety were unique significant predictors of hypertension in African American men. Based on the findings from this study, it is essential healthcare professionals accurately diagnose and treat African American men based on risk factors such as age and anxiety, which may be related to perceived racism and experiences of racism over time. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.